Produção do gênero artigo de opinião no ensino fundamental através de sequências didáticas - Araujo, Adelia Luciana Rangel Botelho de (2015)
This dissertation is an interventionist and applied research aimed to equip students in the 9th grade of elementary education at a public school in the city of João Pessoa-PB, in order to become competent writers and critics of their own texts, through a proposal for teaching and production of the opinion article genre, guided by the approach of didactic sequences. The implementation of this procedure took into account the context of production and reception of that genre and primarily focused on its linguistic and discursive features, from a procedural conception of writing activity. In this perspective, to accomplish our research, we resorted to Bakhtin (1986 [1977], 2011 [1992]) and Marcuschi (2008), regarding the understanding of sociointeractionist nature of language and the concept of textual / discursive genre as well as to Dolz, Noverraz, (2004), regarding the didactic sequence proposal. We also recurred to the contributions of Antunes (2003, 2006, 2009) and Passarelli (2004, 2012), aimed to reflect on the process of teaching and learning of writing at school. The analysis was based on the very textual production of the students involved in the investigation. In this sense, the analysis corpus consisted of ten (10) opinion articles produced by the students, in two versions: in its first version and last, totaling 20 texts. In the analysis of the initial production, we found problems related to the genre structure under study, to the informativeness and to the standard use of the language, which were worked out in the modules / workshops, step envisaged in the didactic sequence proposed. This intervention was followed by the rewriting of the original text, whose difficulties were largely overcome. The results allow us to state that the didactic and pedagogical procedure that we have adopted contributes to develop a linguistic-discursive competence of students.